Facile Synthesis and Size Control of 2D Cyclodextrin‐Based Metal–Organic Frameworks Nanosheet for Topical Drug Delivery. (6th September 2020) - Bello, Mubarak G.; Yang, Yingchao; Wang, Caifen; Wu, Li; Zhou, Panpan; Ding, Huanyu; Ge, Xiaofei; Guo, Tao; Wei, Lai; Zhang, Jiwen
Abstract: In this work, a 2D nanosheet (NS) of γ‐cyclodextrin (CD)‐based metal–organic frameworks (MOFs) is synthesized through a facile green chemistry approach. NS‐MOF carrier is constructed using a water system in a simple one‐pot reaction involving CD and potassium carbonate. Particle size optimization is achieved by adjusting the reaction temperature and the introduction of crystal growth suppressor (appropriate proportion of acetone). The NS‐MOF stability in aqueous medium is improved by polymerization reaction of crosslinked CD‐MOF (CL‐CD‐MOF) without blocking its cavity for drug loading. The effects of particle geometry and size of nanoporous materials on their pharmacokinetics during drug delivery are compared between the sheet‐like DXM@CL‐NS‐MOF and 3D‐cubic‐shaped DXM@CL‐CD‐MOF loaded with the same quantity of dexamethasone (DXM). The bioefficiency of these carriers in tear fluids and aqueous humors to deliver DXM is investigated in vivo. The results demonstrate that the 2D‐nanosheet particles significantly improve precorneal residence time and intraocular bioavailability over the commercial Maxidex (0.1% dexamethasone) and its 3D‐cubes counterpart of similar chemical composition. It suggests that the geometry of a carrier play a significant role in the biodistribution, and the carrier of CL‐NS‐MOF is a good candidate for ocular drug delivery. Abstract : A 2D nanosheet cyclodextrin‐based metal–organic frameworks are synthesized through a simple water‐solvent system, which significantly improves precorneal residence time and intraocular bioavailability over its 3D‐cubes counterpart of similar chemical composition. The result reveals that size and geometry of a carrier play a significant role in a biodistribution.